Feasibility of an intensive control insulin-nutrition glucose model ICING with Malaysian critically-ill patient - Razak N.N.A.; Ahamad N.; Suhaimi F.; Jamaluddin U.; Ralib A.M. (Innovare Academics Sciences Pvt. Ltd, 2023)
glucose; insulin; adult; Article; blood glucose monitoring; critically ill patient; female; glycemic control; health care; hepatic clearance; human; insulin clearance; insulin sensitivity; intensive care unit; intensive glucose nutrition insulin model; major clinical study; Malaysia; male; renal clearance